Biodegradable electrochemical device with barrier layer

JP7936813B2Active Publication Date: 2026-10-16XEROX CORP +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023558628
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-03-31
Filing Date
2022-03-30
Publication Date
2026-10-16
Estimated Expiration
2042-03-30

Smart Images

  • Figure 0007936813000003
    Figure 0007936813000003
  • Figure 0007936813000004
    Figure 0007936813000004
  • Figure 0007936813000005
    Figure 0007936813000005
Patent Text Reader

Abstract

An electrochemical device is disclosed that can include an electrolyte composition disposed between an anode and a cathode, and a water vapor barrier that can include a biodegradable material, the water vapor barrier disposed to prevent water vapor from escaping the electrochemical device. The water vapor barrier can further include polylactic acid or a metallized coating. The water vapor barrier can further include multiple layers and has a water vapor transmission rate (WVTR) of 2% by weight or less over 24 hours. An embodiment of the water vapor barrier can also include a polymeric biodegradable material or a metallized coating disposed on the biodegradable material. The water vapor barrier can also include multiple layers and has a water vapor transmission rate (WVTR) of 1 cm over 24 hours. 2 The composition may also have a water vapor transmission rate (WVTR) of 1 mg / g or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The embodiments or implementations disclosed in this invention relate to biodegradable electrochemical devices, their solid aqueous electrolytes, and moisture barriers therefor. [Background technology]

[0002] The number of batteries produced worldwide is continuously increasing as a result of the growing need for portable and remote power sources. In particular, several new technologies require batteries to power embedded electronic devices. For example, embedded electronic devices such as portable and wearable electronic devices, Internet of Things (IoT) devices, patient medical monitoring, structural monitoring, environmental monitoring, and smart packaging all rely on batteries for power supply. While conventional batteries can be partially recycled, there are currently no environmentally friendly or biodegradable batteries on the market. Therefore, the increased production and use of conventional batteries will result in a corresponding increase in toxic and harmful waste if batteries are not properly disposed of or recycled. Considering the above, there is a need to develop biodegradable batteries, especially for applications where disposable batteries are used for a limited time before disposal.

[0003] Furthermore, to meet the demand for flexible, low-cost, moderately or low-performance batteries, all-printed batteries have been developed and marketed as single-use, disposable batteries. However, none of these all-printed batteries are biodegradable.

[0004] It is generally acknowledged that one of the biggest challenges in the production of biodegradable batteries is the development of biodegradable polymer electrolytes, which are the main polymer-based components of all printed batteries. In addition, a further challenge is the development of such biodegradable polymer electrolytes that can also be printed using existing printing technologies.

[0005] Conventional biodegradable polymer electrolytes often consist of a combination of a biodegradable polymer and a conductive salt. To obtain a biodegradable polymer electrolyte, the biodegradable polymer and conductive salt are dissolved in a solvent, and then the solvent is evaporated at a relatively slow rate to produce a solid polymer electrolyte film. These conventional biodegradable polymer electrolytes often have low ionic conductivity at ambient temperature (e.g., about 10°C at RT) due to the low ion mobility in the biodegradable polymer. -5 There is a problem with conductivity (less than S / cm). However, sufficient conductivity can be achieved when the polymer electrolyte is heated to a temperature sufficient to allow polymer chain mobility (i.e., the operating temperature), thereby allowing ions to move more freely through the polymer electrolyte structure. Sufficient conductivity can also be achieved by incorporating additives that suppress the crystallinity of the polymer electrolyte, but this reduces its operating temperature. Therefore, the number of biodegradable polymer electrolytes that can operate with sufficient conductivity at room temperature is limited.

[0006] In addition to the aforementioned weaknesses, conventional biodegradable polymer electrolytes also suffer from the problem of very long manufacturing processes due to the time required to evaporate the solvent during production. For example, vacuum and / or temperature-assisted evaporation often requires several hours to evaporate the solvent for preparing conventional biodegradable polymer electrolytes, thus limiting the compatibility of conventional biodegradable polymer electrolytes with high-throughput printing processes where consecutive layers must be printed overlapping each other in minutes.

[0007] While printable, biodegradable electrochemical devices, their solid aqueous electrolytes, and methods for synthesizing and fabricating them are available, the layers of various materials, including current collectors, cathode / anode materials, binders, adhesives, and electrolytes, need to be printed with high fidelity and precision. Furthermore, the retention of water or moisture content within the aqueous electrolyte is critical to battery performance through the maintenance of solubilized salts for good ionic conductivity, and printed biodegradable batteries such as these suffer from a shortened lifespan due to moisture loss via evaporation through biodegradable substrates, such as polylactic acid (PLA) films. It is necessary to improve the moisture retention rate of these batteries, particularly the electrolyte layer, by reducing the WVTR (water vapor transmission rate). At the same time, the challenge remains of achieving this sealing characteristic for enclosing electrochemical devices while maintaining or reducing the non-biodegradable material content of biodegradable printed batteries, which is currently not possible using conventional, relatively thick, non-biodegradable foil "pouches" for sealing printed batteries, such as those found in lithium-ion batteries. [Overview of the Initiative]

[0008] The following is a simplified overview to provide a basic understanding of some aspects of one or more embodiments of the teachings of the present invention. This overview is not a lengthy overview, nor is it intended to identify the main or significant elements of the teachings of the present invention, nor does it define the scope of this disclosure. Rather, its primary purpose is simply to present one or more concepts in a simplified form as a prelude to the detailed explanations that will be presented later.

[0009] An electrochemical device is disclosed. The electrochemical device also comprises an anode and a cathode. The device also comprises an electrolyte composition placed between the anode and the cathode, and a water vapor barrier which may include a biodegradable material, the water vapor barrier being placed to prevent water vapor from escaping from the electrochemical device. The water vapor barrier may further include polylactic acid. The water vapor barrier may further include a metallized or aluminum metallized coating. The water vapor barrier may further include multiple layers. The electrochemical device may further have a water vapor transmission rate (WVTR) of 2% by mass or less over 24 hours.

[0010] Embodiments of the water vapor barrier may also include biodegradable materials containing polymers. The water vapor barrier may also include a metallized coating placed on the biodegradable material. The water vapor barrier may contain polymers, which may further include polylactic acid, metallized or aluminum metallized coatings. The water vapor barrier may also include multiple layers, and may withstand 24 hours at a rate of 1 cm 2 It can have a water vapor transmission rate (WVTR) of 1 mg or less per unit.

[0011] The accompanying figures incorporated herein and forming part thereof illustrate embodiments of the teachings of the present invention. These and / or other embodiments and advantages of the embodiments of this disclosure will become apparent and more readily apparent from the following description of various embodiments in conjunction with the accompanying figures. [Brief explanation of the drawing]

[0012] [Figure 1] The diagram shows an exploded view of an exemplary biodegradable electrochemical device in a parallel configuration according to one or more disclosed embodiments. [Figure 2] The diagram shows an exploded view of another exemplary biodegradable electrochemical device in a stacked configuration according to one or more disclosed embodiments. [Figure 3]Figure illustrates a cross-sectional view of a fully assembled surrogate comparative example for a biodegradable battery assembly having a water vapor barrier, in accordance with one or more embodiments. [Figure 4] Figure illustrates a cross-sectional view of a fully assembled surrogate embodiment for the electrochemical device assembly of Example 1 having a water vapor barrier, in accordance with one or more embodiments. [Figure 5] Figure illustrates a cross-sectional view of a fully assembled surrogate embodiment for the electrochemical device assembly of Example 2 having a water vapor barrier, in accordance with one or more embodiments. [Figure 6] Figure illustrates a cross-sectional view of a fully assembled surrogate embodiment for the electrochemical device assembly of Example 3 having a water vapor barrier, in accordance with one or more embodiments. [Figure 7] Figure illustrates a cross-sectional view of a surrogate embodiment for an electrochemical device assembly having a multi-laminate enclosure structure according to the present disclosure. [Figure 8] Figure illustrates a plot of moisture loss per square centimeter (unit: milligrams) versus time (unit: days), in which the comparative example of Figure 3 is compared with Examples 1 to 5 of Figures 4, 5, 6, and 7 respectively. DETAILED DESCRIPTION OF EMBODIMENTS FOR CARRYING OUT THE INVENTION

[0013] It should be noted that some details of the drawings have been simplified and are drawn to facilitate understanding of the teachings of the present invention rather than to maintain strict structural accuracy, details and scale.

[0014] The following description of various exemplary aspects is merely illustrative in nature and is in no way intended to limit the present disclosure, its applications, or uses.

[0015] The ranges used throughout are used as shorthand to describe every and any value that falls within the range. Any value within the range can be selected as the end point of the range. In addition, all references cited in the present specification are hereby incorporated by reference in their entirety. In the event of a conflict between a definition in the present disclosure and a definition in a cited reference, the present disclosure shall prevail.

[0016] Unless otherwise expressly stated, all percentages and amounts expressed herein and elsewhere in the specification should be considered to refer to percentages by mass. The amounts provided are based on the active mass of the material.

[0017] Furthermore, all numerical values are values designated as "about" or "approximately", and take into account experimental errors and variations that would be expected by a person skilled in the art. It should be recognized that all numerical values and ranges disclosed in the present specification are approximate values and ranges, regardless of whether "about" is used concurrently. It should also be recognized that the term "about" as used herein, in conjunction with a numerical value, may refer to a value that is ±0.01% (including the values at both ends), ±0.1% (including the values at both ends), ±0.5% (including the values at both ends), ±1% (including the values at both ends), ±2% (including the values at both ends), ±3% (including the values at both ends), ±5% (including the values at both ends), ±10% (including the values at both ends), or ±15% (including the values at both ends) of that numerical value. It should be further recognized that when a numerical range is disclosed in the present specification, any numerical value falling within the range is also specifically disclosed.

[0018] As used herein, the term “or” is an operator encompassing both values ​​and is equivalent to the term “and / or” unless the context explicitly indicates otherwise. The term “based on” is not exclusive and may be based on further unspecified elements unless the context explicitly indicates otherwise. In the specification, the enumeration “at least one of A, B, and C” includes embodiments containing A, B, or C, multiple examples of A, B, or C, or combinations of A / B, A / C, B / C, A / B / B / B / B / C, A / B / C, etc. In addition, throughout the specification, the meanings of “a,” “an,” and “the” include multiple references. The meaning of “in” includes “in” and “on.”

[0019] Herein, exemplary embodiments of the teachings of the present invention will be mentioned in detail, examples of which are illustrated in the accompanying figures. Wherever possible, the same reference numerals are used throughout the figures to refer to the same, similar, or identical parts.

[0020] Biodegradable electrochemical devices are disclosed herein. As used herein, the terms “biodegradable” or “biodegradable material” may refer to materials, components, substances, devices, etc. that are capable of or designed to be decomposed within a reasonable time by living organisms, particularly microorganisms in waste disposal sites. Materials, components, substances, devices, etc. may decompose into water, naturally occurring gases such as carbon dioxide and methane, biomass, or combinations thereof. As used herein, the expression “biodegradable electrochemical device” or “biodegradable device” may refer to an electrochemical device or a device, respectively, in which at least one or more of its components are biodegradable. In some cases, a large or significant number of components of a biodegradable electrochemical device or biodegradable device are biodegradable. In other cases, all polymer components of a biodegradable electrochemical device or biodegradable device are biodegradable. For example, the polymers and / or other organic-based components of an electrochemical device are biodegradable, while the inorganic materials of an electrochemical device disclosed herein, including metals and / or metal oxides, may not be biodegradable. It should be noted that it is generally accepted that if all polymer and / or organic-based components of an electrochemical device are biodegradable, then the entire electrochemical device is considered biodegradable. As used herein, the term “compostable” may refer to an item that can be composted or otherwise disposed of in an environmentally friendly or ecological manner. Compostable materials can be considered a subset category of biodegradable materials, and further specific environmental temperatures or conditions may be required to break down compostable materials. While the term “compostable” is not synonymous with “biodegradable,” these terms may be used interchangeably if the conditions required to break down or decompose a biodegradable material are considered similar to the conditions required to break down a compostable material. As used herein, the term or expression “electrochemical device” may refer to a device that converts electricity into chemical reactions and / or vice versa.Exemplary electrochemical devices may include, but are not limited to, batteries, photosensitized solar cells, electrochemical sensors, electrochromic glass, fuel cells, electrolysis devices, etc.

[0021] As used herein, the terms or expressions “environmentally friendly electrochemical device” or “environmentally friendly device” may, respectively, refer to an electrochemical device or device that exhibits minimal, lower levels of toxicity to an ecosystem or general environment, or exhibits no toxicity at all. In at least one embodiment, the electrochemical devices and / or components disclosed herein are environmentally friendly.

[0022] As used herein, the terms or expressions “film” or “barrier layer” can refer to, but are not limited to, thin, partially or substantially plastic and / or polymeric materials that can be used as components or parts of various electrochemical devices, including substrates, bonding, enclosures, barriers, or combinations thereof. Films as described herein may be rigid or flexible, depending on the inherent physical properties or dimensions of each of these compositions. In at least one embodiment, these films or barrier layers may be environmentally friendly or biodegradable.

[0023] As used herein, the terms or expressions “enclosure,” “barrier,” or “water vapor barrier” may refer to a material used to prevent moisture, water, or other evaporative materials from entering or leaving through a barrier in an electrochemical device, whether partially sealed or fully sealed. In at least one embodiment, these enclosures may be environmentally friendly or biodegradable.

[0024] As used herein, the term or expression “metallic layer” may refer to a layer of metal on a surface, film, substrate, or barrier layer. Examples of metallic layers described herein may include metallized coatings that can be deposited on a surface by means of vapor or chemical deposition, as well as metal foils, metal films, or other metallic layers combined with or bonded to a surface, film, substrate, or barrier layer.

[0025] In at least one embodiment, the biodegradable electrochemical device disclosed herein may include an anode, a cathode (i.e., a current collector and / or an active layer), and one or more electrolyte compositions (e.g., a biodegradable solid aqueous electrolyte composition). In another embodiment, the biodegradable electrochemical device may further include one or more substrates, one or more sealed parts, one or more packages, one or more pouches, one or more enclosures, or a combination thereof.

[0026] The biodegradable electrochemical devices disclosed herein may be flexible. As used herein, the term “flexible” may mean a material, device, or component thereof that can be bent around a given radius of curvature without breaking and / or cracking. The biodegradable electrochemical devices and / or components disclosed herein can be bent around radii of curvature of about 30 cm or less, about 20 cm or less, about 10 cm or less, and about 5 cm or less without breaking or cracking.

[0027] Figure 1 illustrates an exploded stereoscopic view of an exemplary biodegradable electrochemical device 100 in a parallel or coplanar configuration according to one or more embodiments. As illustrated in Figure 1, the biodegradable electrochemical device 100 may include a first substrate 102, a first current collector 104 and a second current collector 106 adjacent to or on the first substrate 102, an anode active layer 108 adjacent to or on the first current collector 104, a cathode active layer 110 adjacent to or on the second current collector 106, an electrolyte layer 112 adjacent to or on the anode active layer 108 and the cathode active layer 110, and a second substrate 114 adjacent to or on the electrolyte composition 112. It should be noted that the first current collector 104 and the anode active layer 108 may collectively be referred to herein as the anode 120 of the biodegradable electrochemical device 100. It should be further recognized that the second current collector 106 and the cathode active layer 110 may be collectively referred to herein as the cathode 122 of the biodegradable electrochemical device 100. As illustrated in Figure 1, the anode 120 and cathode 122 of the biodegradable electrochemical device 100 may be coplanar such that the anode 120 and cathode 122 are aligned along the same XY plane.

[0028] In at least one embodiment, the biodegradable electrochemical device 100 may include one or more sealing sections (two of which are shown as 116 and 118) that are capable of or designed to seal or airtightly seal the current collectors 104, 106, the anode active layer 108, the cathode active layer 110, and the electrolyte composition 112 between the first substrate 102 and the second substrate 114. For example, as illustrated in Figure 1, the biodegradable electrochemical device 100 may include two sealing sections 116 and 118 inserted between the first substrate 102 and the second substrate 114, as well as around the current collectors 104, 106, the anode active layer 108, the cathode active layer 110, and the electrolyte composition 112, in order to seal or airtightly seal the biodegradable electrochemical device 100. In another embodiment, the biodegradable electrochemical device 100 may not include, or may not substantially include, the sealing portions 116 and 118. For example, the substrates 102 and 114 may be melted or bonded together to seal the biodegradable electrochemical device 100.

[0029] Figure 2 illustrates an exploded stereoscopic view of another exemplary biodegradable electrochemical device 200 having a laminated configuration according to one or more embodiments. As illustrated in Figure 2, the biodegradable electrochemical device 200 may include a first substrate 202, a first current collector 204 disposed adjacent to or on the first substrate 102, an anode active layer 208 disposed adjacent to or on the first current collector 204, an electrolyte layer 212 disposed adjacent to or on the anode 108, a cathode active layer 210 disposed adjacent to or on the electrolyte composition 212, a second current collector 206 disposed adjacent to or on the cathode active layer 210, and a second substrate 214 disposed adjacent to or on the second current collector 206. It should be noted that the first current collector 204 and the anode active layer 208 may be collectively referred to herein as the anode 220 of the biodegradable electrochemical device 200. It should be further recognized that the second current collector 206 and the cathode active layer 210 may be collectively referred to herein as the cathode 222 of the biodegradable electrochemical device 200. As illustrated in Figure 2, the anode 220 and cathode 222 of the biodegradable electrochemical device 200 may be arranged in a stacked configuration or shape such that the anode 220 and cathode 222 are positioned above or below each other.

[0030] In at least one embodiment, the biodegradable electrochemical device 200 may include one or more seals (two of which are shown as 216, 218) that are capable of or designed to hermetically seal the current collectors 204, 206, the anode active layer 208, the cathode active layer 210, and the electrolyte composition 212 between the first substrate 202 and the second substrate 214 of the biodegradable electrochemical device 200. For example, as illustrated in Figure 2, the biodegradable electrochemical device 200 may include two seals 216, 218 inserted between the first substrate 202 and the second substrate 214, as well as around the current collectors 204, 206, the anode active layer 208, the cathode active layer 210, and the electrolyte composition 212, in order to hermetically seal the biodegradable electrochemical device 200. In another embodiment, the biodegradable electrochemical device 200 may not include, or may not substantially include, the sealing portions 216, 218. For example, the substrates 202, 214 may be melted or bonded together to seal the biodegradable electrochemical device 200.

[0031] As illustrated in Figures 1 and 2, each of the current collectors 104, 106, 204, and 206 may include tabs 124, 126, 224, and 226 that extend outside the sealed portions 116, 118, 216, and 218 to provide coupling.

[0032] In at least one embodiment, one or more of the substrates 102, 114, 202, and 214 of each biodegradable electrochemical device 100, 200 may be, or include, biodegradable substrates, but are not limited to these. Exemplary biodegradable substrates may be, or include, one or more of polylactic acid (PLA), polylactic acid-co-glycolic acid (PLGA), silk fibroin, chitosan, polycaprolactone (PCL), polyhydroxybutyrate (PHB), rice paper, and cellulose, or a combination or composite thereof.

[0033] The biodegradable substrates of each of the biodegradable electrochemical devices 100, 200 can be stable at temperatures of approximately 50°C to approximately 150°C. As used herein, the terms “stable” or “reliable” can refer to the ability of a substrate to resist dimensional changes and maintain structural integrity when exposed to temperatures of approximately 50°C to approximately 150°C. For example, a biodegradable substrate can be made to maintain or be designed to maintain structural integrity with dimensional changes of less than approximately 20%, less than approximately 15%, or less than approximately 10% after exposure to temperatures of approximately 50°C to approximately 150°C. In one example, each of the biodegradable substrates can be stable at temperatures of approximately 50°C, approximately 60°C, approximately 70°C, approximately 80°C, approximately 90°C, approximately 100°C, or approximately 110°C to approximately 120°C, approximately 130°C, approximately 140°C, or approximately 150°C (e.g., dimensional changes of less than 20%). In another example, each of the biodegradable substrates can be stable at temperatures of at least 100°C, at least 105°C, at least 110°C, at least 115°C, at least 120°C, at least 125°C, at least 130°C, at least 135°C, at least 140°C, or at least 145°C. In at least one embodiment, the biodegradable substrate can be stable at temperatures of about 50°C to about 150°C for a period of about 5 minutes to about 60 minutes or more. For example, the biodegradable substrate can be stable at the aforementioned temperatures for a period of about 5 minutes, about 10 minutes, about 20 minutes, or about 30 minutes to about 40 minutes, about 45 minutes, about 50 minutes, or about 60 minutes or more.

[0034] In at least one embodiment, the biodegradable substrates are weldable, bondable, and / or permanently thermally sealable without the use of further adhesives. For example, each of the biodegradable substrates 102, 114, 202, and 214 can be weldable and / or bondable to one another without the use of their respective seals 116, 118, 216, and 218. Exemplary biodegradable substrates that can be weldable and / or bondable to one another may include, but are not limited to, thermoplastics such as polylactic acid (PLA), polylactic acid modified with nucleating agents that enhance crystallinity, such as polylactic acid modified with nucleating agent D (PLA-D) and polylactic acid modified with nucleating agent E (PLA-E), polybutylene succinate (PBS), polybutylene adipate terephthalate (PBAT), blends of PLA and polyhydroxybutyrate (PHB), PHB-based blends, or combinations thereof, or may include these. As used herein, the terms or expressions “joinable,” “weldable,” and / or “permanently thermally sealed” may refer to the ability of a material (e.g., a substrate) to heat-seal or permanently bond two surfaces together by heating or melting.

[0035] The anode active layers 108, 208 of each biodegradable electrochemical device 100, 200 may be, but are not limited to, one or more of zinc (Zn), lithium (Li), carbon (C), cadmium (Cd), nickel (Ni), magnesium (Mg), magnesium alloys, zinc alloys, etc., or combinations thereof and / or alloys thereof, or may contain these. The exemplary anode active layer or its material may be, but are not limited to, these, etc., or combinations thereof, or may contain these. In at least one embodiment, the anode active layer may contain a sufficient amount of zinc oxide (ZnO) to regulate or control H2 gas generation.

[0036] In at least one embodiment, the anode active layers 108, 208 of the biodegradable electrochemical devices 100, 200, respectively, can be prepared or fabricated from an anode paste. For example, the anode active layer can be prepared from a zinc anode paste. The anode paste can be prepared in an attritor mill. In at least one embodiment, stainless steel shot can be placed in the attritor mill to facilitate the preparation of the anode paste. The anode paste may include one or more metals or metal alloys, one or more organic solvents, one or more styrene-butadiene rubber binders, or a combination thereof. In exemplary embodiments, the anode paste may include one or more of ethylene glycol, styrene-butadiene rubber binders, zinc oxide (ZnO), bismuth(III) oxide (Bi2O3), Zn dust, or a combination thereof. Exemplary organic solvents are known in the art and are not limited to these, but may include ethylene glycol, acetone, NMP, or a combination thereof, or may include these. In at least one embodiment, one or more biodegradable binders can be used instead of or in combination with the styrene-butadiene rubber binder.

[0037] The cathode active layers 110 and 210 of the biodegradable electrochemical devices 100 and 200, respectively, may be, but are not limited to, one or more of the following: iron (Fe), iron(VI) chloride, mercury oxide (HgO), manganese(IV) oxide (MnO2), carbon (C), carbon-containing cathode, gold (Au), molybdenum (Mo), tungsten (W), molybdenum trioxide (MoO3), silver oxide (Ag2O), copper (Cu), vanadium oxide (V2O5), nickel oxide (NiO), copper iodide (Cu2I2), copper chloride (CuCl), or combinations and / or alloys thereof, or may contain these. In exemplary embodiments, the cathode active layers 110 and 210 may contain manganese(IV) oxide. Carbon and / or carbon-containing cathode active layers can be used in aqueous metal-air batteries, such as zinc-air batteries.

[0038] In at least one embodiment, the cathode active layers 110, 210 may include one or more additives capable of or designed to at least partially enhance the electronic conductivity of the cathode active layers 110, 210. Exemplary additives may include, but are not limited to, carbon particles, such as graphite, carbon nanotubes, carbon black, or a combination thereof, or may include these.

[0039] In at least one embodiment, the cathode active layers 110, 210 of the biodegradable electrochemical devices 100, 200, respectively, can be prepared or fabricated from a cathode paste. For example, the cathode active layers 110, 210 can be prepared from a manganese(IV) oxide cathode paste. The cathode paste can be prepared in an attritor mill. In at least one embodiment, stainless steel shot can be placed in the attritor mill to facilitate the preparation of the cathode paste. The cathode paste may include one or more metals or metal alloys, one or more organic solvents (e.g., ethylene glycol), one or more styrene-butadiene rubber binders, or a combination thereof. In exemplary embodiments, the cathode paste may include one or more of ethylene glycol, styrene-butadiene rubber binders, manganese(IV) oxide (MnO2), graphite, or a combination thereof. Exemplary organic solvents are known in the art and are not limited to these, but may include ethylene glycol, acetone, NMP, or a combination thereof, or may include these. In at least one embodiment, one or more organic solvents may be replaced with an aqueous solvent, such as water, or used in combination therewith. For example, water can be used in combination with manganese(IV) oxide.

[0040] The anode and / or cathode paste may have a viscosity of about 100 cP to about 1E6 cP. For example, the anode and / or cathode paste may have a viscosity of about 100 cP or more, about 200 cP or more, about 500 cP or more, about 1,000 cP or more, about 1,500 cP or more, about 2,000 cP or more, about 10,000 cP or more, about 20,000 cP or more, about 50,000 cP or more, about 1E5 cP or more, about 1.5E5 cP or more, about 2E5 cP or more, about 3E5 cP or more, about 4E5 cP or more, about 5E5 cP or more, about 6E5 cP or more, about 7E5 cP or more, about 8E5 cP or more, or about 9E5 cP or more. In another example, the anode and / or cathode paste may have a viscosity of about 200 cP or less, about 500 cP or less, about 1,000 cP or less, about 1,500 cP or less, about 2,000 cP or less, about 10,000 cP or less, about 20,000 cP or less, about 50,000 cP or less, about 1E5 cP or less, about 1.5E5 cP or less, about 2E5 cP or less, about 3E5 cP or less, about 4E5 cP or less, about 5E5 cP or less, about 6E5 cP or less, about 7E5 cP or less, about 8E5 cP or less, about 9E5 cP or less, or about 1E6 cP or less.

[0041] In at least one embodiment, each of the anodes 120, 220 and cathodes 122, 222, or their active layers 108, 110, 208, 210, may independently contain a biodegradable binder. The function of the biodegradable binder is to fix each particle of each layer together, resulting in adhesion to the subsurface of the substrate, where each layer is the anode current collector 104, 204, the cathode current collector 106, 206, the anode active layer 108, 208, the cathode active layer 110, 210, or a combination thereof. Exemplary biodegradable binders are, but are not limited to, one or more of chitosan, polylactic acid-co-glycolic acid (PLGA), gelatin, xanthan gum, cellulose acetate-butyrate (CAB), polyhydroxybutyrate (PHB), or a combination thereof, or may include these. In at least one embodiment, one or more of the biodegradable polymers disclosed herein with respect to the electrolyte composition may also be used as biodegradable binders for anodes 120, 220, cathodes 122, 222, their components, or any combination thereof. Furthermore, as described herein, one or more biodegradable polymers may be crosslinked. Thus, the biodegradable binders used for anodes 120, 220, cathodes 122, 222, and / or their components may include crosslinked biodegradable binders disclosed herein with respect to the electrolyte composition.

[0042] The respective electrolyte layers 112 and 212 of the respective biodegradable electrochemical devices 100 and 200 may be or contain an electrolyte composition. The electrolyte composition may utilize a biodegradable polymer material. The electrolyte composition may be a solid or aqueous electrolyte composition. The solid or aqueous electrolyte composition may be a copolymer hydrogel and a salt dispersed in and / or throughout the hydrogel, or contain these. The copolymer may contain at least two polycaprolactone (PCL) chains bonded to a polymer central block (CB). For example, the copolymer may be a block copolymer or graft copolymer containing at least two PCL chains coupled to the polymer central block, e.g., PCL-CB-PCL. In another example, the copolymer may be a block copolymer or graft copolymer containing at least one of polylactic acid (PLA), polyglycolic acid (PGA), polyethyleneimine (PEI), or a combination thereof, coupled to the polymer central block.

[0043] The copolymer or solid may be present in the hydrogel in an amount of about 5% to 90% by mass relative to the total mass of the hydrogel (e.g., the total mass of the solvent, polymer, and salt). For example, the copolymer may be present in an amount of about 5% to 10% to 15% to 20% to 25% to 30% to 35% to 10% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 15% to 16% to 15% to 16% to 17% to 16% to 17% to 18

[0044] The copolymer may be present in the hydrogel in an amount sufficient to provide a continuous film or layer that is free of or substantially free of air bubbles. The copolymer may also be present in an amount sufficient to give the hydrogel a viscosity of about 1,000 cP to about 100,000 cP. For example, the copolymer may be present in the hydrogel in an amount sufficient to give the hydrogel a viscosity of about 1,000 cP, about 5,000 cP, about 10,000 cP, or about 20,000 cP to about 30,000 cP, about 40,000 cP, about 50,000 cP, about 75,000 cP, about 90,000 cP, or about 100,000 cP.

[0045] The polymer central block of the copolymer may be a biodegradable polymer, thereby improving or increasing the biodegradability of the solid, aqueous electrolyte composition. The biodegradable polymer of the polymer central block is preferably naturally occurring. The polymer central block may be, contain, or be derived from a biodegradable polymer containing at least two free hydroxyl groups available for reaction with a polymer, such as ε-caprolactone. Furthermore, as described herein, a polymer containing at least two free hydroxyl groups can be reacted with ε-caprolactone to form a copolymer. Exemplary polymers containing at least two free hydroxyl groups that can be utilized to form the polymer central block (CB) may be, but are not limited to, one or more of polyvinyl alcohol (PVA), hydroxyl-retaining polysaccharides, biodegradable polyesters, hydroxy fatty acids (e.g., castor oil), or a combination thereof. Exemplary hydroxyl-retaining polysaccharides may include, but are not limited to, starch, cellulose, carboxymethylcellulose, methylcellulose, hydroxyethylcellulose, chitin, guar gum, xanthan gum, agar, pullulan, amylose, alginic acid, dextran, or combinations thereof, or may contain these. Exemplary biodegradable polyesters may include, but are not limited to, polylactic acid, polyglycolic acid, polylactic acid-co-glycolic acid, polyitaconic acid, polybutylene succinate, or combinations thereof, or may contain these. In preferred embodiments, the polymer central block may be one or more of polyvinyl alcohol (PVA), hydroxyl-retaining polysaccharides, biodegradable polyesters, or hydroxy fatty acids, or may contain these.

[0046] In at least one embodiment, the polymer center block of the copolymer does not have to be a biodegradable polymer. For example, the polymer center block of the copolymer may be, but is not limited to, polyethylene glycol (PEG), hydroxy-terminated polyester, hydroxyl-terminated polyolefin, such as hydroxyl-terminated polybutadiene, or a combination thereof, or may include these.

[0047] A copolymer comprising at least two polycaprolactone (PCL) chains bonded to a polymer central block may be a graft copolymer or a block copolymer. Whether a copolymer is a graft copolymer or a block copolymer can be determined at least partially by the number and / or arrangement of at least two free hydroxyl groups on the polymer central block. For example, a graft copolymer is formed when ε-caprolactone is reacted with a polymer central block having hydroxyl groups on the monomer along the length of the polymer central block chain. In another example, a block copolymer is formed when ε-caprolactone is reacted with a polymer central block having hydroxyl groups at each end of the polymer central block. Exemplary block copolymers may be triblock copolymers, tetrablock copolymers, starblock copolymers, or combinations thereof, or may include these.

[0048] As discussed above, the electrolyte composition may be a solid, aqueous electrolyte composition comprising a copolymer hydrogel and a salt dispersed in the hydrogel. The salt of the hydrogel may be any suitable ionic salt known in the art, or may include such salts. Exemplary ionic salts may be, but are not limited to, one or more of organic-based salts, inorganic-based salts, ionic liquids at room temperature, deep eutectic solvent-based salts, or combinations or mixtures thereof, or may include such salts. In preferred embodiments, the salt is a salt usable in zinc / manganese(IV) oxide (Zn / MnO2) electrochemistry, or includes such salts. Exemplary salts, though not limited to these, may include zinc chloride (ZnCl2), ammonium chloride (NH4Cl), sodium chloride (NaCl), phosphate-buffered saline (PBS), sodium sulfate (Na2SO4), zinc sulfate (ZnSO4), manganese sulfate (MnSO4), magnesium chloride (MgCl2), calcium chloride (CaCl2), ferric chloride (FeCl3), lithium hexafluorophosphate (LiPF6), potassium hydroxide (KOH), sodium hydroxide (NaOH), or combinations thereof, or may contain these. In a preferred embodiment, the salt of the electrolyte composition may be ammonium chloride (NH4Cl), zinc chloride (ZnCl2), or combinations or mixtures thereof, or may contain these. In another embodiment, the salt may be an alkali metal salt, such as sodium hydroxide (NaOH), ammonium hydroxide (NH4OH), potassium hydroxide (KOH), or combinations or mixtures thereof, or may contain these.

[0049] The salt may be present in an amount that is possible to produce ionic conductivity, an amount designed to produce ionic conductivity, or an amount sufficient to produce ionic conductivity. For example, the salt may be present in the hydrogel in an amount or concentration of at least 0.1 M, more preferably at least 0.5 M, even more preferably at least 2 M, and even more preferably at least 4 M. The salt may be present in the hydrogel in a concentration of 10 M or less, more preferably at least 6 M. In another example, the salt may be present in the hydrogel in an amount of about 3 M to about 10 M, about 4 M to about 10 M, about 5 M to about 9 M, or about 6 M to about 8 M. In an exemplary embodiment, the salt included ammonium chloride and zinc chloride. In this case, ammonium chloride was present in an amount of about 2.5 M to about 3 M, about 2.8 M to about 2.9 M, or about 2.89 M, and zinc chloride was present in an amount of about 0.5 M to 1.5 M, about 0.8 M to about 1.2 M, or about 0.9 M.

[0050] In at least one embodiment, the electrolyte composition may include one or more additives. These additives may include, but are not limited to, biodegradable or environmentally friendly nanomaterials. Biodegradable nanomaterials may provide and / or improve the structural strength of the electrolyte layer or its composition without sacrificing its flexibility, or may be designed to do so. Exemplary biodegradable nanomaterials may include, but are not limited to, polysaccharide-based nanomaterials, inorganic nanomaterials, or combinations thereof, or may include these. Exemplary polysaccharide-based nanomaterials may include, but are not limited to, one or more of cellulose nanocrystals, chitin nanocrystals, chitosan nanocrystals, starch nanocrystals, or combinations or mixtures thereof, or may include these. Exemplary inorganic nanomaterials may include, but are not limited to, one or more of silicon dioxide (e.g., fumed silica), aluminum oxide, layered silicates, or lime, or combinations or mixtures thereof, or may include these. Exemplary layered silicates may include, but are not limited to, one or more of the following: bentonite, kaolinite, dickite, nacrite, attapulgite, illite, halloysite, montmorillonite, hectorite, fluorohectorite, nontronite, bydelite, saponite, volconscoreite, magadiite, medmontite, kenyaite, soaconite, muscovite, vermiculite, mica, hydromica, phengite, bramalite, and celadonite, or combinations or mixtures thereof, or may contain any of these.

[0051] One or more additives may be present in an amount of at least 0.1% by mass relative to the total mass of the hydrogel. For example, one or more additives may be present in an amount of at least 0.1% by mass, at least 0.5% by mass, or at least 1% by mass relative to the total mass of the hydrogel. One or more additives may also be present in an amount of 40% by mass or less relative to the total mass of the hydrogel. For example, one or more additives may be present in an amount of 40% by mass or less, 20% by mass or less, or 10% by mass or less relative to the total mass of the hydrogel.

[0052] In at least one embodiment, the electrolyte composition may contain an aqueous solvent. For example, the electrolyte composition may contain water. In at least one embodiment, the electrolyte composition may contain a co-solvent. For example, the electrolyte composition may contain water and a further solvent. Exemplary co-solvents may be, but are not limited to, one or more of ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, or a combination thereof, or may contain these. The co-solvent may contain water in an amount of about 20%, about 30%, about 40%, about 50% to about 60%, about 70%, about 80%, about 85%, or about 90% by total mass or volume of the aqueous solvent in the electrolyte composition.

[0053] In at least one embodiment, the electrolyte composition comprises a copolymer hydrogel and a salt dispersed in the hydrogel, a solvent (e.g., water or water and a cosolvent), one or more photoinitiators, one or more optional additives, or a combination thereof. For example, the electrolyte composition comprises a copolymer hydrogel, a salt dispersed in the hydrogel, a solvent, one or more additives, or a combination or mixture thereof. In at least one embodiment, the electrolyte composition consists of or is essentially composed of a copolymer hydrogel, a salt dispersed in the hydrogel, and a solvent (e.g., water or water and a cosolvent). In another embodiment, the electrolyte composition consists of or is essentially composed of a copolymer hydrogel, a salt dispersed in the hydrogel, a solvent, and one or more additives. The solvent, which may be water or a combination of water and a cosolvent, can bring the hydrogel to equilibrium. Suitable electrolyte compositions and methods and procedures for producing them are disclosed in International Application PCT / US2020 / 046932, the disclosure of which is incorporated herein by reference in its entirety.

[0054] As previously discussed, the electrolyte layers 112 and 212 of the biodegradable electrochemical devices 100 and 200, respectively, may be or contain solid or aqueous electrolyte compositions. The solid or aqueous electrolyte compositions can possess sufficient mechanical and electrochemical properties required for commercially available printed batteries or commercially useful printed batteries. For example, the solid or aqueous electrolyte compositions may have a Young's modulus or storage modulus greater than about 0.10 megapascals (MPa), greater than about 0.15 MPa, or greater than about 0.20 MPa, thus providing a solid or aqueous electrolyte composition with sufficient strength while maintaining sufficient flexibility to prevent failure under stress. The solid or aqueous electrolyte compositions may have a Young's modulus of about 100 MPa or less, about 80 MPa or less, about 60 MPa or less, or lower.

[0055] As used herein, the term or expression “yield strength” may refer to the maximum stress that a material can or cannot withstand before it begins to deform permanently. Solid and aqueous electrolyte compositions may have a yield strength of about 5 kPa or more. For example, solid and aqueous electrolyte compositions may have a yield strength of about 5 kPa or more, about 8 kPa or more, about 10 kPa or more, about 12 kPa or more, about 15 kPa or more, or about 20 kPa or more.

[0056] The solid, aqueous electrolyte composition can be electrochemically stable with respect to both the anode active layers 108, 208 and the cathode active layers 110, 210, respectively, of the biodegradable electrochemical devices 100, 200. For example, the solid, aqueous electrolyte composition can maintain a stable no-load voltage over a long period of time, thereby demonstrating electrochemical stability with respect to both the anode active layers 108, 208 and the cathode active layers 110, 210, respectively, of the biodegradable electrochemical devices 100, 200. In at least one embodiment, the solid, aqueous electrolyte composition can remain electrochemically stable in contact with the electrode layers for at least one month, at least two months, at least three months, at least four months, at least five months, at least six months, at least one year, or longer.

[0057] The solid, aqueous electrolyte compositions disclosed herein can be used in any electrochemical device, such as an electrochemical cell, a battery, and / or the biodegradable electrochemical devices 100, 200 disclosed herein. In preferred embodiments, the solid, aqueous electrolyte compositions can be used in a battery comprising a Zn anode active layer and a MnO2 cathode active layer.

[0058] The current collectors 104, 106, 204, and 206 of the biodegradable electrochemical devices 100 and 200, respectively, may be capable of receiving, conducting, and delivering electricity, or may be designed to do so. Exemplary current collectors 104, 106, 204, and 206 may be, but are not limited to, silver, e.g., silver microparticles and silver nanoparticles; carbon, e.g., carbon black, graphite, carbon fibers, carbon nanoparticles, e.g., carbon nanotubes, graphene, reduced graphene oxide (RGO), etc., or any combination thereof, or may include these.

[0059] method Embodiments of this disclosure can provide a method for fabricating electrochemical devices, such as the biodegradable electrochemical devices 100, 200 disclosed herein. The method may include a step of preparing a biodegradable substrate. The method may also include a step of depositing electrodes and / or electrode compositions adjacent to or on the biodegradable substrate. The electrode depositing step may include a step of depositing and drying the electrode current collector, and a step of depositing and drying the active layer (i.e., anode or cathode material) adjacent to or on the current collector. The method may also include a step of drying the electrodes and / or electrode compositions. The electrode compositions may be thermally (e.g., by heating) dried. The method may also include a step of depositing a biodegradable, radiation-curable electrolyte composition on or adjacent to the electrode composition. The method may further include a step of radiation-curing the biodegradable radiation-curable electrolyte composition. The biodegradable radiation-curable electrolyte composition may be radiation-cured before or after drying the electrode composition. The biodegradable substrate may be thermally compatible with any thermal drying. For example, a biodegradable substrate can be dimensionally stable (e.g., without bending and / or curling) when thermally dried. The method may include the step of depositing a second electrode and / or electrode composition on or adjacent to a biodegradable, radiation-curable electrolyte composition. In at least one embodiment, each of the first and second electrode compositions is a metal foil composition. The metal foil composition of the first electrode may be different from the metal foil composition of the second electrode.

[0060] In at least one embodiment, an electrochemical device, all or substantially all of its components, are manufactured via a printing process. The printing process may include deposition, stamping, spraying, sputtering, jetting, coating, lamination, etc. For example, one or more current collectors, one or more electrode compositions, biodegradable, radiation-curable electrolyte compositions, or combinations thereof may be deposited via a printing process. Exemplary printing processes may include, but are not limited to, one or more of screen printing, inkjet printing, flexographic printing (e.g., stamping), gravure printing, offset printing, airbrushing, aerosol printing, typesetting, roll-to-roll, etc., or combinations thereof, or include these. In a preferred embodiment, the components of the electrochemical device are printed via screen printing.

[0061] In at least one embodiment, the step of radiation-curing a biodegradable radiation-curable electrolyte composition includes the step of exposing the electrolyte composition to radiant energy. The radiant energy may be ultraviolet light. By exposing the biodegradable radiation-curable electrolyte composition to radiant energy, the biodegradable radiation-curable electrolyte composition can be at least partially crosslinked, thereby forming a hydrogel. The biodegradable radiation-curable electrolyte composition can be cured by radiation at room temperature. In at least one embodiment, the biodegradable radiation-curable electrolyte composition is cured in an inert atmosphere. For example, the biodegradable radiation-curable electrolyte composition can be cured under nitrogen, argon, etc. In another embodiment, the biodegradable radiation-curable electrolyte composition may be cured in a non-inert atmosphere.

[0062] In at least one embodiment, a biodegradable radiation-curable electrolyte composition can be cured by radiation for a period of about 5 ms to about 100 ms. For example, a biodegradable radiation-curable electrolyte composition can be cured by radiation for a period of about 5 ms, about 10 ms, about 15 ms, about 20 ms, about 30 ms, about 40 ms, or about 50 ms to about 60 ms, about 70 ms, about 80 ms, about 85 ms, about 90 ms, about 95 ms, or about 100 ms. The period of time sufficient to cure the biodegradable radiation-curable electrolyte composition by radiation can be determined at least in part by the output of ultraviolet light.

[0063] In at least one embodiment, the method may also include the step of depositing an adhesive, such as a biodegradable adhesive, thereby obtaining the respective seals 116, 118, 216, and 218 of the biodegradable electrochemical devices 100 and 200. For example, the method may include the step of depositing a layer of adhesive to couple the substrate or a portion of the substrate of the electrochemical device (e.g., the peripheral areas of tabs 124, 126, 224, and 226) to each other. In some embodiments, the adhesive may be a hot-melt adhesive. In other embodiments, the electrochemical device may not contain any adhesive, or may substantially not contain any adhesive. For example, the biodegradable substrate may be weldable and / or heat-sealable without the use of further adhesives.

[0064] In at least one embodiment, the biodegradable substrate may be a continuous web or supported by a continuous web. As used herein, the term “web” may refer to a moving support surface, such as a conveyor belt. In at least one example, multiple electrochemical devices are printed simultaneously as independent or linked elements or components on a continuous web. For example, each component of multiple electrochemical devices may be printed simultaneously as independent or linked components on a continuous web as a single array in a parallel process. As used herein, the terms or expressions “linked element” or “linked component” may refer to each element or component of electrochemical devices that are physically touching, overlapping, or otherwise in contact with one another. An exemplary linked element may be, or include, an active layer (e.g., a cathode active layer or an anode active layer) positioned adjacent to or on a current collector layer, a current collector layer and copper tape tabs, or an electrolyte layer on an active cathode / anode layer.

[0065] In at least one embodiment of an exemplary biodegradable electrochemical device, its solid aqueous electrolyte, as well as methods for synthesizing and fabricating it, are available, and layers of various materials, including current collectors, cathode / anode materials, binders, adhesives, and electrolytes, need to be printed with high fidelity and precision. Furthermore, the water retention rate within the aqueous electrolyte is critical to battery performance through the maintenance of solubilized salts for good ionic conductivity, and such biodegradable or compostable printed batteries have the problem of shortened lifespan due to water loss via evaporation through a biodegradable substrate, which may be a polylactic acid (PLA) film. Such electrochemical devices may have a biodegradable polymer composite film enclosure pouch with a biodegradable barrier layer. Exemplary biodegradable enclosure materials may include, but are not limited to, one or more of the following: polylactic acid (PLA), polylactic acid-coglycolic acid (PLGA), silk fibroin, chitosan, polycaprolactone (PCL), polyhydroxybutyrate (PHB), rice paper, and cellulose, or combinations or composites thereof, or may contain any of these.

[0066] In at least one embodiment, a flexible biodegradable electrochemical device comprising an electrolyte composition containing an anode, a cathode, and a crosslinked biodegradable polymer material crosslinked between the anode and cathode and radiation-curable before printing, may have a biodegradable moisture or water vapor barrier or barrier layer forming an enclosure, film, or pouch around the outer portion of the electrochemical device to prevent the evaporation of moisture present in the aqueous electrolyte material. In such embodiments, since the entire electrochemical device is biodegradable, the device may have a long service life, be biodegradable, and / or remain biodegradable even after its service life has ended, due to improved properties of the water vapor barrier or moisture barrier layer of the enclosure pouch. The function of the biodegradable water vapor barrier or enclosure is to provide a moisture barrier layer that prevents water from evaporating from the aqueous electrolyte composition within the electrochemical device, thereby extending the service life of the electrochemical device. In relation to the water vapor barrier or moisture barrier layer described herein, certain embodiments of the electrochemical device may contain a substantial amount of water or moisture, while other solvents or evaporative materials may also contribute to the long-term and acceptable operation of the electrochemical device enclosed within the water vapor barrier of the Disclosure.

[0067] The biodegradable water vapor barrier of each biodegradable electrochemical device can be stable at temperatures of approximately 50°C to approximately 150°C. As used herein, the terms “stable” or “reliable” may refer to the ability of a substrate to resist dimensional changes and maintain structural integrity when exposed to temperatures of approximately 50°C to approximately 150°C. For example, a biodegradable water vapor barrier can be made to maintain or be designed to maintain structural integrity with dimensional changes of less than approximately 20%, less than approximately 15%, or less than approximately 10% after exposure to temperatures of approximately 50°C to approximately 150°C. In one example, each biodegradable water vapor barrier can be stable at temperatures of approximately 50°C, approximately 60°C, approximately 70°C, approximately 80°C, approximately 90°C, approximately 100°C, or approximately 110°C to approximately 120°C, approximately 130°C, approximately 140°C, or approximately 150°C (e.g., dimensional changes of less than 20%). In another example, each of the biodegradable water vapor barriers can be stable at temperatures of at least 100°C, at least 105°C, at least 110°C, at least 115°C, at least 120°C, at least 125°C, at least 130°C, at least 135°C, at least 140°C, or at least 145°C. In at least one embodiment, the biodegradable water vapor barrier can be stable at temperatures of about 50°C to about 150°C for periods of about 5 minutes to about 60 minutes or more. For example, the biodegradable water vapor barrier can be stable at the aforementioned temperatures for periods of about 5 minutes, about 10 minutes, about 20 minutes, or about 30 minutes to about 40 minutes, about 45 minutes, about 50 minutes, or about 60 minutes or more.

[0068] In at least one embodiment, the biodegradable water vapor barrier material is weldable, bondable, and / or permanently thermally sealable without the use of further adhesives. For example, the biodegradable water vapor barriers described herein for electrochemical device enclosures may be weldable and / or bondable to one another without the use of separate seals. Exemplary biodegradable water vapor barrier materials that may be weldable and / or bondable to one another may include, but are not limited to, thermoplastics such as polylactic acid (PLA), polylactic acid modified with nucleating agents that enhance crystallinity, such as polylactic acid modified with nucleating agent D (PLA-D) and polylactic acid modified with nucleating agent E (PLA-E), polybutylene succinate (PBS), polybutylene adipate terephthalate (PBAT), blends of PLA and polyhydroxybutyrate (PHB), PHB-based blends, or combinations thereof, or may include these. As used herein, the terms or expressions “joinable,” “weldable,” and / or “permanently thermally sealed” may refer to the ability of a material (e.g., a substrate) to heat-seal or permanently bond two surfaces together by heating or melting.

[0069] In some embodiments, biodegradable enclosures, pouches, or water vapor barriers can be fabricated from metallized biodegradable polylactic acid (PLA) films, such as aluminum metallized polylactic acid films. The metallized surface layer providing the metallization may be aluminum. In certain embodiments, the metallized layer may include aluminum, other suitable metals or alloys, ceramics, clay, inorganic-organic biopolymer hybrid materials, and combinations thereof. Alternative embodiments may have a metal multilayer, metal on the inner layer, outer layer, or both of the multilayer film. The PLA film may be biaxially oriented to improve the physical properties of the enclosure pouch. In yet another embodiment, additives that enhance moisture barrier properties may be incorporated into the film. Biodegradable enclosures, pouches, or water vapor barriers for electrochemical devices may have a single or multilayer having one or more combinations of materials in the alternative embodiments. The metallized layer film or barrier can offer thicknesses of about 1 nm to about 100 nm, about 5 nm to about 50 nm, or about 10 nm to about 40 nm. A single-layer film or barrier of a particular example may have a total thickness of approximately 1 μm to 100 μm, approximately 40 μm to 80 μm, or approximately 50 μm to 75 μm. The metallized layer of the water vapor barrier may have a thickness of approximately 0.5 nm to 100 nm, approximately 5 nm to 50 nm, or approximately 5 nm to 25 nm on a substrate film layer, for example, PLA.

[0070] In certain examples, a biodegradable enclosure, pouch, or water vapor barrier may be made of a multilayer composite constructed by extruding or laminating a biodegradable polymer onto each side of a thin metal foil, such as aluminum. In contrast to the metallized polymer layer of a biodegradable enclosure, thin and continuous metal layers within such a multilayered laminated composite can provide a strong barrier layer linked to one or more biodegradable enclosure layers. The advantages of such a multilayered laminated structure are that the continuous metal film forms a layer that can more effectively prevent water permeation through the composite, and that it provides the option of providing a thicker metal or aluminum layer or metal multilayer. Thus, the metal layer providing the water vapor barrier is Approximately 0.1μm to approximately 10μm, approximately 20μm to approximately 150μm, The thickness can be approximately 1 μm to 200 μm, or approximately 5 μm to 150 μm, or approximately 10 μm to 100 μm. The metal foil layer according to this disclosure is less prone to problems such as pinholes in the aluminum or metal layer (which are commonly found in metal films formed from sputtering or other deposition methods such as those described herein). The presence of pinholes in the metal layer or other barrier layer within a biodegradable enclosure, pouch, or water vapor barrier can, in some cases, allow some water to permeate through the composite material.

[0071] For certain examples having multilayer composite materials according to the present disclosure, these multilayer laminates can be formed using several methods. In a first embodiment, a pre-existing polymer sheet can be pressed onto one or each side of an aluminum sheet at appropriate temperature and pressure using one or more interlocking or dispersed adhesive bonding layers that enable or enhance the adhesion of the polymer sheet to aluminum or metal foil. In a second embodiment, the polymer layer and adhesive bonding layer can be directly melt-extruded as a thin film onto the surface of aluminum or other metal foil using multilayer film casting methods known to those skilled in the art. Further metal foils or films incorporating metals, such as magnesium, titanium, iron, nickel, copper, zinc, or alloys or mixtures thereof, can be used in accordance with the present disclosure.

[0072] In certain embodiments, other materials known to have water vapor barrier properties can be used. These materials must conform to a biodegradable and / or compostable format and must include materials such as beeswax, plasticizers, and alternative biodegradable polymer composite films. In alternative embodiments where the water vapor barrier is not part of the substrate of the electrochemical device, a water vapor barrier with higher temperature stability and resistance, having a wider range of temperature resistance compared to biodegradable materials, polymers, or composites, can be used. Embodiments of a biodegradable enclosure with water vapor barrier properties or an electrochemical device having a water vapor barrier can exhibit lower water vapor transmission rates (WVTR) compared to an electrochemical device without such a barrier, layer, or enclosure, showing WVTRs of approximately 0% to approximately 5% over 24 hours, approximately 0.1% to approximately 2% over 24 hours, or approximately 0.5% to approximately 1% over 24 hours. WVTR can also be expressed as the percentage of the total mass of water lost compared to the total mass of the electrochemical device including the enclosure or moisture barrier. Embodiments of electrochemical devices having a biodegradable enclosure or water vapor barrier with moisture barrier properties according to this disclosure can exhibit a lower water vapor transmission rate (WVTR) compared to electrochemical devices without such a barrier layer or enclosure, where the water vapor barrier is approximately 0.0 g / m³ 2 / 24 hours ~ approx. 10g / m 2 / 24 hours, approximately 0.5g / m 2 / 24 hours ~ approx. 5g / m 2 / 24 hours, or approximately 1 g / m 2 / 24 hours ~ approx. 2g / m 2 / 24 hours. The expression of WVTR is provided herein as weight percent, or wt%, of the entire electrochemical device. Certain examples of the electrochemical device having a biodegradable enclosure with moisture barrier properties or a water vapor barrier can exhibit lower water vapor transmission rate (WVTR) when compared to an electrochemical device without such a barrier layer or enclosure, and the water vapor barrier of the present disclosure has a WVTR of about 0 mg / cm 2 / 24 hours to about 5.0 mg / cm 2 / 24 hours, about 0.1 mg / cm 2 / 24 hours to about 1 mg / cm 2 / 24 hours, or about 0.1 mg / cm 2 / 24 hours to about 0.5 mg / cm 2 / 24 hours.

[0073] In some embodiments, the electrochemical device may be arranged such that the battery or electrochemical device is fully contained within the enclosure or within the described water vapor barrier having improved water vapor barrier properties, and the cathode and the anode may be oriented or arranged to have a parallel or lateral XY planar configuration as illustrated in Figure 1. In alternative embodiments, the electrochemical device may be arranged such that the battery or electrochemical device is contained within the described enclosure having improved water vapor barrier properties, and the cathode and the anode may be oriented or arranged to have a stacked configuration as illustrated in Figure 2.

[0074] Embodiments of the present disclosure can provide a method for fabricating, generating, or otherwise encapsulating an electrochemical device having improved moisture barrier properties or water vapor barrier properties. The method includes the step of orienting a first metallized PLA film having four edges and a second metallized PLA film having four edges such that the non-metallized side of the first metallized PLA film faces the non-metallized side of the second metallized PLA film. One or more edges of the first and second metallized PLA films can also be sealed together. A biodegradable or compostable electrochemical device can be placed between the first metallized PLA film and the second metallized PLA film, and subsequently, the edges of the first metallized PLA film and the edges of the second metallized PLA film can be sealed together such that one or more electrodes of the electrochemical device are exposed through at least one of the four edges.

[0075] Alternatively, the method may include the step of orienting a first metallized PLA film having four edges on the upper side of the electrochemical device, with the non-metallized side facing the electrochemical device. A second metallized PLA film is oriented on the bottom side of the electrochemical device, with the non-metallized side facing the electrochemical device. All four edges of the first metallized PLA film and the four edges of the second metallized PLA film can also be sealed together so that one or more electrodes are exposed through at least one of the four edges. Enclosures or water vapor barriers fabricated in this manner from a biodegradable aluminized polymer barrier layer can be combined with surface coatings and / or polymer additives to reduce or prevent water vapor loss from biodegradable or compostable electrochemical devices. Such devices can significantly extend the service life of biodegradable or compostable electrochemical devices by preventing the evaporation of electrolyte solvents over time. [Examples]

[0076] The examples and other implementations described herein are illustrative and are not intended to limit the full scope of the compositions and methods disclosed herein. Equivalent variations, modifications, and alterations of specific implementations, materials, compositions, and methods can be produced within the scope of this disclosure and produce substantially similar results.

[0077] (Comparative Example 1) A substitute test relating to the embodiments described herein of a biodegradable battery configuration with improved moisture retention is described in relation to Comparative Example 1. Figure 3 illustrates a cross-sectional view of a comparative example of a fully assembled substitute for a biodegradable battery assembly with a water vapor barrier, according to one or more embodiments. This substitute test was performed to measure moisture loss through a PLA-D biodegradable substrate under conditions similar to those of a fully assembled biodegradable battery. Comparative Example 1 is a substitute battery assembly 300 having a film enclosure 304 surrounding a patch of filter paper 302 as a substitute for an aqueous electrolyte battery composition. Two sheets of biaxially oriented film of 80 μm thick PLA-D were cut into 2 cm × 3 cm squares. The two cut films were laminated together in the same orientation. Using an MTI MSK-130 heat sealing device set to 170°C for 5 seconds, three of the four edges of a film sheet were heated and sealed together to produce a single, unsealed pouch or enclosure with a 3cm side. A 1cm square patch of whatman1825-150 filter paper 302 was placed in a 2cm × 3cm pouch 304. The pouch with the filter paper 302 inside was then weighed, and the tare weight was measured. Three drops of DI water were added to the paper inside the pouch, and then the remaining open edge of the pouch was sealed to form a heated and sealed edge 306 under the same conditions as previously described. The mass of the pouch was measured over time to determine the water loss. The surrogate test involves the production of a full-size, sealed substrate configuration and the addition of a known, measured amount of water that reflects the same amount found in a fully assembled biodegradable battery. Next, the moisture loss over time is measured by periodically weighing the substitute battery assembly 300. Then, various embodiments of the film enclosure for inhibiting water permeation loss from the aqueous-based electrolyte composition in the biodegradable electrochemical device are evaluated by repeating this test protocol using experimental examples 1 to 3.

[0078] (Example 1) Figure 4 illustrates a cross-sectional view of a fully assembled substitute embodiment for an electrochemical device assembly of Example 1 having a water vapor barrier according to one or more embodiments. Two 4cm × 4cm square sheets of Enviromet HS, 75 μm thick aluminized PLA from Celplast, Toronto Ontario, Canada are laminated together, oriented with the PLA sides facing inward to form an enclosure 400 for the electrochemical device. Three of the four edges of the sheets are sealed together using an MSK-130 heat sealing apparatus with a soft die set to 170°C for 3 seconds to produce an enclosure pouch 400 with one side open, creating an enclosure pouch 400 having an inner PLA layer 410 and an outer aluminum layer 412. Next, a PLA-D enclosure pouch 404, with its edges sealed in the same manner as described in the embodiment relating to water-soaked filter paper 402 and Comparative Example 1, was placed inside the PLA-Al pouch 400, and the remaining edges 414 were sealed using MSK-130. The mass of pouch 400 over time was measured to determine the moisture loss.

[0079] (Example 2) Figure 5 illustrates a cross-sectional view of an embodiment of a fully assembled substitute for an electrochemical device assembly of Example 2 having a water vapor barrier according to one or more embodiments. Eight 4cm × 4cm square sheets of Enviromet, 75 μm thick aluminized PLA, were oriented and laminated together to form an enclosure pouch or water vapor barrier 500 having four layers for the electrochemical device, with the PLA sides facing inward. Using an MSK-130 heat sealing apparatus with a soft die set to 170°C for 3 seconds, three of the four edges of each sheet were sealed together to produce an enclosure pouch 500 with one side open. In this embodiment, the walls of the enclosure pouch 500 consist of a first layer having a first PLA layer 508 and a first aluminum layer 510, a second layer having a second PLA layer 512 and a second aluminum layer 514, a third layer having a third PLA layer 516 and a third aluminum layer 518, and a fourth layer having a fourth PLA layer 520 and a fourth aluminum layer 522, creating four laminated sheets of Enviromet aluminized PLA. Then, similar to the embodiment described with respect to Comparative Example 1, the water-soaked filter paper 502 and the PLA-D enclosure pouch 504, sealed at the edge 506, were placed inside the PLA-Al pouch 500, and the remaining edge 522 was sealed using MSK-130. The mass of the enclosure pouch 500 over time was measured to determine the moisture loss.

[0080] (Example 3) Figure 6 illustrates a cross-sectional view of a fully assembled substitute embodiment for an electrochemical device assembly of Example 3 having a water vapor barrier according to one or more embodiments. Enviromet, two 4cm × 4cm square sheets of 75μm thick aluminized PLA were oriented and laminated together to form an enclosure pouch 600 with the PLA sides facing inward and having a single water vapor barrier layer for the electrochemical device. Using an MSK-130 heat sealing apparatus with a soft die set to 170°C for 3 seconds, three of the four edges were sealed together to produce an enclosure pouch 600 with one side open. In this embodiment, the walls of the enclosure pouch 600 consist of a PLA layer 604 and an aluminum layer 606. A 1cm square patch of Whatman 1825-150 filter paper 602 was placed inside the 4cm × 4cm enclosure pouch 600. Next, pouch 600, which has paper patch 602 inside, was weighed, and its tare weight was measured. Three drops of DI water were added to paper 602 in pouch 600, and then the last open edge of the pouch was sealed with MSK-130 as before. The mass of the pouch over time was measured to determine the moisture loss.

[0081] (Examples 4, 5, 6, and 7) Figure 7 illustrates a cross-sectional view of an embodiment of a substitute for an electrochemical device assembly having a multi-laminate enclosure structure according to the present disclosure. In the multilayer enclosure structure 700, the first and second sides of the metal barrier layer 702 have a first adhesive bonding layer 704 and a second adhesive bonding layer 706 positioned on the metal barrier layer 702. Note that in certain material configurations for the multilayer composite structure 700, no adhesive bonding layers are required, but in other embodiments, the presence of adhesive bonding layers may be desirable in cases where the polymer would not adhere to an aluminum or other metal surface without adhesive. In certain examples, the compositions of the adhesive bonding layers 704, 706 are biodegradable, however, since they are sufficiently thin compared to the metal and polymer layers, these layers may be fabricated partially or entirely from non-biodegradable materials. In such examples, the relative mass percentage of any non-biodegradable material is less than 10% of the mass of the total enclosure material. In certain examples, the aluminum or metal barrier 702 surface may have a surface treatment, such as plasma or corona treatment, which can enhance adhesion to the surface of one or multiple metal barrier layers 702. While it is also expected that both the outer first biodegradable polymer layer 708 and the second biodegradable polymer layer 710 are constructed of the same material, in certain examples the first biodegradable polymer layer 708 and the second biodegradable polymer layer 710 do not have to be constructed of the same material, and therefore the material compositions of the adhesive bonding layers 704, 706 may differ if required to optimize adhesion with each type of polymer used in the first biodegradable polymer layer 708 and the second biodegradable polymer layer 710. The metal layers or metal barrier layers described herein provide multilayer enclosure structures having a water-impermeable layer, or a layer that does not allow water to pass through. In certain examples of such multilayer enclosure structures, the metal layers or metal barrier layers may also make it impossible for any water, moisture, or solvent to pass through the enclosure.

[0082] Example 4: Production of a half-structure multilayer composite using a commercially available 3-layer PLA thin film as the adhesion layer. A PLA sheet approximately 100 μm thick was obtained by melt extrusion of a mixture of commercially available extruded grade PLA obtained from Corbion and a crystallizing agent (agent D, Luminy D070, manufactured by Corbion). A multilayer stack was prepared using 40 μm thick aluminum foil obtained from All Foils Inc., Ohio, USA, an extruded PLA-D polymer sheet, and a 3-layer PLA thin film, Evlon EV-HS1, as the adhesive bonding layer between them. This multilayer stack was compressed at 120°C and 5000 PSI for 20 minutes. The resulting multilayer film is considered to be half of the multilayer structure detailed in Figure 7. However, since the aluminum layer acts as a water vapor barrier layer, this half-structure is sufficient to demonstrate the barrier properties in the evaluation of the substitute according to this disclosure. A complete structure may only be required in certain embodiments to protect the aluminum layer from mechanical damage by adding a scratch-resistant polymer layer. The complete structure can be fabricated using the same method as the half-structure.

[0083] Example 5: Production of a semi-structured multilayer composite using a non-biodegradable polyamide-based adhesive as the bonding layer. A thin layer of polyamide-based adhesive powder (Evonik Vestamelt Hylink) was coated onto a 40 μm thick aluminum foil using an electrostatic spray gun, and then placed in an oven at 140°C for 10 minutes. Next, the obtained PLA-D sheet, as detailed in Example 4, was applied to the adhesive bonding layer side of the aluminum foil and compressed at 120°C and 5000 PSI for 20 minutes. The adhesive bonding layer was 2 mg / cm² by mass. 2 In contrast, the mass of the half-structure is 32.4 mg / cm³. 2 The mass of the adhesive bonding layer was approximately 6% by mass relative to the total mass of the half-structure. Therefore, the mass of the adhesive bonding layer in the fully symmetrical multi-laminate structure was 54.4 mg / cm³. 2 4 mg / cm³ 2 Alternatively, it can be calculated as 7.4% by mass of the non-biodegradable adhesive bonding layer.

[0084] Example 6: Production of a half-structure of a multilayer composite using a thin film of polycaprolactone (PCL) as an adhesive bonding layer. CAPA6500 PCL pellets obtained from Ingevity were compressed at 100°C and 5000 PSI for 20 minutes to obtain a thin film of the PCL adhesive bonding layer. A multilayer stack was prepared using 40 μm thick aluminum foil, a sheet of PLA-D used in Example 4 and extruded according to this disclosure, and the PCL thin film as the adhesive bonding layer. The multilayer stack was compressed at 120°C and 5000 PSI for 20 minutes.

[0085] Example 7: Production of a semi-structured multilayer composite material using a thin film of amorphous grade PLA as an adhesive bonding layer. A thin film of amorphous PLA layer was produced by compressing PLA pellets at 200°C and 5000 PSI for 20 minutes. A multilayer stack was prepared using 40 μm thick aluminum foil, an extruded PLA-D sheet (as in Example 4), and alternatingly interlocked amorphous PLA thin films as the adhesive bonding layer. The multilayer stack was compressed at 120°C and 5000 PSI for 20 minutes.

[0086] In certain embodiments, the multilayer composites of Examples 6 and 7 can be produced in a single step by directly melt-extruding a double layer of adhesive bonding layer and PLA film onto an aluminum roll, as is commonly practiced in the multilayer packaging manufacturing industry.

[0087] To demonstrate the barrier properties of the multilayer composites produced in Examples 4, 5, 6, and 7, airtight pouches of each multilayer laminate (half-structure) were prepared by cutting out sheets of similar dimensions and thermally sealing their edges by compressing them between the interlocking parts of a handheld heat sealer set to 200°C for 5 seconds. Each pouch contained a water-soaked paper structure. The mass of each pouch was then measured daily as a means of monitoring water permeation and subsequent evaporation through the multilayer composite.

[0088] Figure 8 shows a plot of moisture loss per square centimeter (in milligrams) versus time (in days), comparing the comparative example in Figure 3 with Examples 1-7 in Figures 4, 5, 6, and 7. For each example, the cumulative moisture loss per square centimeter (in milligrams) was measured by mass every 24 hours, normalized against the surface area, and then plotted. Comparative Example 1, which has only a PLA-D substrate as a barrier layer, has a moisture loss of approximately 15 mg / cm². 2 This shows a high cumulative moisture loss, and the total moisture loss by day 9 is shown. Example 1, which has an additional aluminized PLA barrier layer, showed a moisture loss of approximately 1.34 mg / cm³ by day 9. 2 This shows a significantly reduced cumulative moisture loss. Example 2, which has four combined aluminized PLA barrier layers, showed a cumulative moisture loss of 0.66 mg / cm³ by day 9. 2 This shows a significant decrease. Example 3, which has only aluminized PLA as the barrier layer, showed a cumulative water loss of 2.84 mg / cm³ on day 9 compared to the total water loss of Comparative Example 1 over a similar period of time. 2 This shows a moderately improved reduction. The multi-laminate samples of Examples 4, 5, 6, and 7 showed virtually no moisture loss or only very slight moisture loss by day 9. All results are reported in Tables 1 and 2.

[0089] [Table 1]

[0090] [Table 2]

[0091] Continuity Test The use of embodiments of biodegradable batteries having a barrier layer as described herein presents potential problems affecting the continuity of the battery tab, particularly with regard to the use of heat sealing across the entire tab. This was evaluated by constructing several full-size batteries using aluminized PLA as the outer barrier layer, similar to Example 2. Using a low temperature of 135°C for the MSK sealer provided a stronger seal while preventing unnecessary heat exposure and potential damage to the battery tab. The MSK sealer was set to a low temperature of 135°C, in soft mode, for a longer period of 6 seconds. The devices were found to be fully functional with no loss of continuity across the entire tab after heat sealing.

[0092] This disclosure is based on illustrative implementations. While a limited number of implementations are shown and described, those skilled in the art will recognize that modifications may be made to these implementations without departing from the principles and spirit of the preceding detailed description. All such modifications and alterations are intended to be construed as being included in this disclosure, insofar as they fall within the scope of the appended claims or their equivalents.

Claims

1. anode, Cathode, An electrolyte composition placed between the anode and the cathode and A biodegradable printed cell comprising two water vapor barriers made of biodegradable material, positioned on both sides of a layer containing an anode and a cathode, wherein the water vapor barriers made of biodegradable material are arranged to reduce the amount of vapor escaping from the biodegradable printed cell. The biodegradable printed battery has a water vapor transmission rate (WVTR) of 1 mg or less per cm² for 24 hours.

2. The biodegradable printed battery according to claim 1, wherein the water vapor barrier further comprises polylactic acid (PLA).

3. The biodegradable printed battery according to claim 1, wherein the water vapor barrier further comprises a metallized coating.

4. The biodegradable printed battery according to claim 3, wherein the metallized coating contains aluminum.

5. The biodegradable printed battery according to claim 1, further comprising a metal layer having a water vapor barrier thickness of 1 μm to 150 μm.

6. The biodegradable printed battery according to claim 1, wherein the anode is printed directly onto a water vapor barrier.

7. The biodegradable printed battery according to claim 1, wherein the cathode is printed directly onto a water vapor barrier.

8. anode, Cathode, An electrolyte composition placed between the anode and the cathode, and A biodegradable printed battery comprising two water vapor barriers made of biodegradable material, positioned on both sides of a layer containing an anode and a cathode, A water vapor barrier containing biodegradable materials is placed to prevent water vapor from escaping from the biodegradable printed battery. A water vapor barrier containing biodegradable materials further comprises a polylactic acid (PLA) layer and a metal layer. Biodegradable printed batteries last for 24 hours, 1 cm 2 A biodegradable printed battery having a water vapor transmission rate (WVTR) of 1 mg or less per unit area.

9. The biodegradable printed battery according to claim 8, wherein the metal layer has a thickness of 0.1 μm to 10 μm.

10. The biodegradable printed battery according to claim 8, wherein the metal layer has a thickness of 20 μm to 150 μm.

Citation Information

Patent Citations

  • External packing material for cells, external packing shell for cells and preparation method thereof, and cell

    CN110391359A

  • Flexible lithium ion battery

    CN209418692U

  • Cell

    JP2001155694A

  • Packaging material for battery

    JP2014049307A

  • Multi-layer high moisture barrier polylactic acid film

    US20110076511A1